LOAD BALANCING DINAMIS MENGGUNAKAN ALGORITMA DYNAMIC DISTRIBUTION UPON DEMAND PADA SISTEM ENKRIPSI/DEKRIPSI DATA TERDISTRIBUSI - Laulyta, Lauw Reduardy I.; Fajar, Mohammad; Bahri, Syamsul (Institute of Research and Community Outreach - Petra Christian University, 2015)
The diversity of capability of computers worker in distributed system influences resource allocation and completion time for each jobs on the system. This study aims to implement a dynamic load balancing technique using dynamic distribution upon demand (DDD) algorithm to optimize the resource allocation in distributed data encryption/decryption system. Evaluating was performed by comparing the proposed system with two other models that is a system without load balancing and with static load balancing method. Evaluation result showed that the resource allocation in the proposed system using DDD algorithm more optimized and at the decryption process of three and four characters with proper workload initialization values presented that the job completion time much faster than the two other systems.